2003
DOI: 10.1308/003588403322520735
|View full text |Cite
|
Sign up to set email alerts
|

Do patients expect too much from extracorporeal shock wave lithotripsy?

Abstract: This was a simple and cost-effective exercise, that has generated some valuable data which can be used to improve the entire patient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…If expectations are too high disappointment will follow. 8 The statistically equal and high rating given to staff attitude and information gives emphasis to the importance of both these factors. The relatively low priority given to pain control was not anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If expectations are too high disappointment will follow. 8 The statistically equal and high rating given to staff attitude and information gives emphasis to the importance of both these factors. The relatively low priority given to pain control was not anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study will enable us to put the appropriate 'weight' on the results of patient satisfaction surveys in order to allocate resources and improve service appropriately. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Ghalayini et al [36] found that patients were more satisfied with surgical procedures that had higher stone clearance. Others, as addressed earlier, have revealed discrepancies with their a priori assumptions about what was important to patients and their satisfaction with surgery [19,20], finding that stone clearance is not always most important. In a small study of their patients who had undergone percutaneous nephrolithotomy, Staios et al [37] found that HRQOL improved in only half of patients who had been rendered stone free.…”
Section: Incorporating Hrqol In Stone Surgerymentioning
confidence: 98%
“…Both Kouriefs and Quatan conducted studies that revealed unclear and perhaps unreasonable patient expectations regarding stone clearance following SWL. More importantly, these same authors were surprised as stone clearance was rated as more important than pain control by their patients [19,20], thus indicating an alternate view to that of the urologist.…”
Section: Urolithiasis and Treatment Expectationsmentioning
confidence: 99%
“…Trotz der relativ hohen Komplikationsrate wurde die Behandlung von mehr als 93% der Patienten als Erfolg eingestuft. Quatan et al [25] haben als Hauptgrund für die Unzufriedenheit die nicht erreichte Steinfreiheit angeführt.…”
Section: Introductionunclassified